2008
DOI: 10.1111/j.1461-0248.2007.01149.x
|View full text |Cite
|
Sign up to set email alerts
|

Species’ traits predict the effects of disturbance and productivity on diversity

Abstract: Disturbance is an important factor influencing diversity patterns. Ecological theory predicts that diversity peaks at intermediate levels of disturbance, but this pattern is not present in a majority of empirical tests and can be influenced by the level of ecosystem productivity. We experimentally tested the effects of disturbance on diversity and show that species' autecological traits and community relations predicted species loss. We found that - alone or in concert - increasing disturbance intensity or fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
197
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(209 citation statements)
references
References 44 publications
(83 reference statements)
9
197
2
1
Order By: Relevance
“…However, our observation of dominant Actinobacteria populations in low-organic matter soils suggests that this may not be the case. It has been suggested that fastgrowing copiotrophic microorganisms that primarily use labile carbon sources are likely to most rapidly and positively respond to nutrient inputs (Ramirez et al, 2012), and that intrinsic growth rate is the main factor leading to success following disturbance (Haddad et al, 2008). However, we show that positive response to nutrient addition in the presence of hydrocarbon contaminants is not limited to specific groups, but that different bacterial taxa are favoured depending on environmental factors, in this case, organic matter content.…”
Section: Discussioncontrasting
confidence: 43%
“…However, our observation of dominant Actinobacteria populations in low-organic matter soils suggests that this may not be the case. It has been suggested that fastgrowing copiotrophic microorganisms that primarily use labile carbon sources are likely to most rapidly and positively respond to nutrient inputs (Ramirez et al, 2012), and that intrinsic growth rate is the main factor leading to success following disturbance (Haddad et al, 2008). However, we show that positive response to nutrient addition in the presence of hydrocarbon contaminants is not limited to specific groups, but that different bacterial taxa are favoured depending on environmental factors, in this case, organic matter content.…”
Section: Discussioncontrasting
confidence: 43%
“…Indeed, in some communities where disturbance reduces or has no effect on diversity at small spatial scales, diversity at larger spatial scales is actually enhanced because a matrix of sites favouring species with complementary ecological requirements is created (Cadotte 2007;Berry et al 2008). The pertinent scale of this effect is likely determined by the dispersal abilities of the study organism (Shea, Roxburgh & Rauschert 2004;Haddad et al 2008), and for trees we expect infrequent colonization events beyond several hundred metres up to several kilometres (Nathan & Muller-Landau 2000;Sheil & Burslem 2003). Therefore, it is important to consider the spatial distribution of gaps in the studied forest, especially when assessing appropriate interventions for forest management.…”
Section: I S T U R B a N C E A N D T R E E D I V E R S I T Y I N M mentioning
confidence: 99%
“…in composition among stems that will live to reproduce and contribute to subsequent generations (Shea, Roxburgh & Rauschert 2004;Haddad et al 2008). Indeed several tests of the intermediate disturbance hypothesis in tropical trees (e.g.…”
Section: I S T U R B a N C E A N D T R E E D I V E R S I T Y I N M mentioning
confidence: 99%
“…Because different plant species are adapted to the availability of distinct nutrients in the soil, the type and number of limiting resources can affect species composition and richness (Critchley et al 2002;Venterink et al 2003;Harpole & Tilman 2007). Disturbances also affect species richness and composition, as well as altering the influence that species traits have on plant establishment and development (Haddad et al 2008). Whereas soil properties and fire can alter the functional traits and species composition of plant communities (Müller et al 2007;Silva & Batalha 2008), plants may also alter soil conditions through processes such as nitrogen fixation, nutrient cycling, and aluminum detoxification, and indirectly by the volume and quality of litter deposition (Göttlein et al 1999;Gessner et al 2010).…”
Section: Introductionmentioning
confidence: 99%